2015
DOI: 10.14419/ijet.v4i4.5405
|View full text |Cite
|
Sign up to set email alerts
|

Effect on superhydrophobic surfaces on electrical porcelain insulator, improved technique at polluted areas for longer life and reliability

Abstract: This paper proposes a novel technique to enhance the stability of high-voltage insulators, which are affected due to the presence of dust, contamination, electrical stresses in a high moisture content environment. These result in puncture of insulators and heavy loss due to power outages in the transmission lines. To extend its stability, powdered coating is done on the insulators which have insulation property and super hydrophobicity. In this paper, the authors were inspired by the 'lotus effect', and a nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…FTIR examination of pure one-dimensional silica structures reveals two bond types occurring in the chemical structure of SiO 2 nanowires including Si-O-Si and Si-O, which correspond to the following values of the wavenumber: 451, 802, 964, and 1072 cm −1 , respectively. This coincides with the results obtained in the works [ 40 , 41 ]. In addition, the peaks obtained in the FTIR spectrum, which were obtained for bimodal SiO 2 /SiO 2 nanowires, correspond to the bonds present in the chemical structure of the reinforcing phase.…”
Section: Resultssupporting
confidence: 93%
“…FTIR examination of pure one-dimensional silica structures reveals two bond types occurring in the chemical structure of SiO 2 nanowires including Si-O-Si and Si-O, which correspond to the following values of the wavenumber: 451, 802, 964, and 1072 cm −1 , respectively. This coincides with the results obtained in the works [ 40 , 41 ]. In addition, the peaks obtained in the FTIR spectrum, which were obtained for bimodal SiO 2 /SiO 2 nanowires, correspond to the bonds present in the chemical structure of the reinforcing phase.…”
Section: Resultssupporting
confidence: 93%
“…For SiO 2 -Ag, there is a broad band located near 3400 cm −1 and another located at 1627 cm −1 , both corresponding to the O–H stretching of water and the formed silanol groups (Si–OH), respectively [ 92 , 93 ]. The bands observed at 1100 and 475 cm −1 , on the other hand, are attributed to symmetrical stretching and bending of Si–O–Si bonds, respectively [ 92 , 94 , 95 ]. The peaks located at 950 and 845 cm −1 indicate the bending of the O–Si–O moiety [ 80 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…SEM and TEM images of the SiO 2 and TiO 2 nanoparticles showed average diameters of 75.1 and 113.5 nm, respectively. PL, UV-vis absorbance and FT-IR spectra of the sterilized SiO 2 and TiO 2 nanoparticles showed that the spectroscopic properties of the nanoparticles did not significantly change from previously reported data after the sterilization processes [31][32][33]. After the characterization of the sterilized SiO 2 and TiO 2 nanoparticles, 2D and 3D human normal colon fibroblast CCD-18Co cells were used to monitor their cytotoxicity.…”
Section: Discussionmentioning
confidence: 81%